Penerapan Sanksi Kepada Perusahaan Yang Tidak Melaksanakan Corporate Social Responsibility (CSR) Terhadap Pekerja - Luh Made Ramadia Sari; Ida Bagus Erwin Ranawijaya (Jurnal Hukum dan Sosial Politik, 2023)
Basically Corporate Social Responsibility (CSR) is manifested in the social role of a company or Limited Liability Company (PT) towards the company's internal environment, namely the welfare of its workers' lives. The existence of a level of welfare for workers is one way or strategy that can increase the participation of workers, motivation and loyalty of the workers. This problem is included in the Law of the Republic of Indonesia Number 40 of 2007 concerning Limited Liability Companies and in addition to the Law Number 25 of 2007 concerning Investment (UUPM) Article 34, namely "companies that invest in are required to implement CSR" to create conditions that are harmonious, balanced and in accordance with the environment, norms, and culture, as well as the Law that regulates the Social Security System and which establishes the Employment Social Security Administering Agency as an institution that regulates all labor guarantees for all Indonesian people, namely BPJS employment. The purpose of this writing is; 1). Providing a form of CSR responsibility to the company for the welfare of the workers; 2). Implement sanctions given to companies if they do not carry out CSR responsibilities to employees. This method uses writing in the form of normative legal methods or in legal research literature from the results of a study, there is one main thing that can be concluded. Namely, there are several rules that regulate corporate social responsibility, there is a law on State-Owned Enterprises (BUMN), an investment law and a social security law. a requirement for CSR that has the potential to cause multiple interpretations in practice, because not all laws that have regulated and contain rules that are subject to sanctions in it.